Diseño del Centro de Memoria Espacios De Cultura Reconciliación En El Municipio De Agustín Codazzi - Cesar - Báez Contreras, Luis Alejandro; Ampique García, Karen Milena (Universidad Antonio Nariño, 2024)
Propia